Medication Related Burden pada Pasien Gagal Ginjal Kronis di RSUD Kota Yogyakarta : Medication Related Burden in Patients with Chronic Kidney Failure at the Yogyakarta City Hospital - Woro Supadmi; Muhammad Muhlis; Ilham Bintang Agung (Jurnal Sains dan Kesehatan, 2021)
Chronic kidney disease (CKD) is a condition of chronic kidney function decline, progressive and irreversible. Treatment measures given to patients with chronic kidney disease depends on what stage obtained from treatment of comorbid conditions to renal replacement or hemodialysis. Prolonged drug consumption affects the burden of medication or medication related burden on patients. This study was conducted to determine the relationship between treatment load and the level of adherence in patients with chronic renal failure in RSUD Kota Yogyakarta. This study was observational study with a cross-sectional design. The instrument used was in the form of LMQ questionnaire to determine medication related burden and questionnaire MARS to determine the adherence. Data were analyzed by Spearman Test to determine the relationship between medication-related burden and patient compliance. The results showed that significant correlation between LMQ scores and MARS scores (correlation coefficient = -0.413, p = 0.001) and between VAS Score and MARS scores (correlation coefficient = -0.413, p = 0.001). The higher the medication related burden, the lower the patient's compliance.